The relationship between readiness and the usage of e-learning among English Lecturers / Farah Idayu Mohd Salleh ... [et al.] - Mohd Salleh, Farah Idayu; Baharum, Harmi Izzuan; Shamsudin, Sarimah; Md. Ghazali, Jamilahtun; Mohd Raidzuan, Syazwa Nabila (Penerbit UiTM (UiTM Press), 2015)
Nowadays, e-learning becomes useful to learning institutions worldwide, and because of that, an assessment of e-learning readinessis essential for the successful implementation of e-learning as a platform for learning. Success in e-learning can be achieved by understanding the level of readiness of e-learning environments. University of Kuala Lumpur already facilitate each campus with e-learning facilities and conducting workshop to the students and lecturers. Still, not all lecturers are ready to use e-learning in their teaching process. This study was carried out to examine UniKL English lecturers'readiness in the usage of e-learning. For this purpose, English lecturers of University of Kuala Lumpur will be given an online questionnaire on the usage of e-learning in their teaching process. For data collection, one set of online questionnaire was designed. The questionnaires were distributed to 51 English lecturers at UniKL but only 30 responded to the online questionnaires. The overall findings of this research shows that English lecturers prefer to use traditional way which is face-to-face medium to teach English, even though they are ready to embrace e-learning in their teaching process due to few constrains. The study revealed a positive relationship between the facilities of e-learning at the University of Kuala Lumpur and English lecturers' acceptance of using e-learning in their teaching process.